Comparison of Conventional Methods and Automated Systems for Determining Antibiotic Susceptibility of Bacteria Isolated from Urine Culture (Bangladesh Journal of Medical Science, 2019)
Objective: The aim of our study was to compare the results obtained from different methods, which are used to determine the susceptibility to antimicrobials, and to determine the agreement between them.Materials and Methods: A total of 397 strains consisting of 329 gram negative and 68 gram positive bacteria that were isolated from urine samples and identification and antibiogram of which were performed by automated systems, were included in the study. The results obtained from broth microdilution, E test, VITEK and disk diffusion were compared.Results: Our antimicrobial susceptibility test results in gram negative bacteria showed a categorical agreement of 93.3% with a very major error rate of 1.5 in disk diffusion test, while a categorical agreement of 90% with a very major error rate of 2.2% in Vitek 2 test. The agreement for E test was 95.3% with a very major error rate of 1.1. In the antimicrobial susceptibility test of gram positive bacteria, the rate of agreement for disk diffusion, E test and Vitek 2 was 97.2%, 98.4% and 95.4% respectively. Very major error rate was found % 1.5 ve % 2.6 in disk diffusion and Vitek 2, respectively, while no very major error was found in E test.Conclusions: In conclusion, our data suggest that disk diffusion test, Vitek 2 system and E test test are accurate and acceptable for antibiotic susceptibility tests of gram positive bacteria. The agreement rate of BMD and E test methods was found above 90% for all antibiotics, and it was reached a conclusion that the susceptibility results of gram negative bacteria for ceftriaxone and nitrofurantoin obtained from VITEK; the susceptibility results of disk diffusion test for ceftriaxone and ciprofloxacin should be confirmed by a more reliable method.Bangladesh Journal of Medical Science Vol.18(3) 2019 p.519-526